Pengaruh Salep Ekstrak Kulit Buah Mangga Arumanis ( Mangifera Indica L ) Terhadap Luka Infeksi Pseudomonas Aeruginosa Secara In-Vivo - Ifmaily Ifmaily; Sanubari Rela Tobat; Tiara Febria; Putri Rizki Fitriani (Jurnal Ventilator, 2024)
Arumanis mango rind is an organic waste that contains secondary metabolites such as flavonoids. Many flavonoids are found in the rind of the arumanis mango, which acts as a very strong antioxidant and has the potential to heal wounds, including infected wounds. This study aims to determine the effect of arumanis mango (Mangifera indica L.) rind extract ointment on healing infected wounds caused by Pseudomonas aeruginosa bacteria, determine the effective concentration for healing infected wounds, and the histopathological decripstions. This research was an experimental study using male white rats which were divided into 5 groups, namely group I (control), group II (Gentamicin), group III (5% concentration), group IV (10% concentration) and group V (15% concentration). The parameters observed were the percentage of healing of infected wounds, epithelialization time, and histopathology. Then the data were analyzed using the ANOVA test followed by Duncan's further test.The results of the study were based on the group order above, from the parameters the average percentage of infected wound healing on 3rd day was 29.73%; 48.84%; 45.95%; 42.81%; 42.33%, on 7th day it was 70.96%; 85.79%; 83.25%; 76.95%; 73.87%, and on the 14th day it was 89.89%; 93.32%; 93.87%; 92.67%; 91.48%. Epithecization time is 9; 6; 7; 8; 9 (day), for histopathology of fibroblast cells with a score of 1; 3; 3; 2; 2; for collagen fibers 1; 3; 3; 3; 3; for re-epithelialization 2; 3; 2; 2; 2; for inflammatory cells 0; 3; 2; 2; 2. The conclusion of the research is that arumanis mango peel extract ointment (Mangifera indica L.) has an influence on the healing process of wounds infected by Pseudomonas aeruginosa bacteria in male white mice, the most effective concentration and the best histopathological descriptions at a concentration of 5%.